Am nevoie de ajutor
2/13×{5/2×[6/23×(5/2-2/3-7/8)+3/4]-1/3}=
Răspunsuri la întrebare
Răspuns de
1
2/13×{5/2×[6/23×(5/2-2/3-7/8)+3/4]-1/3}== 2/13 x {5/2 x [6/23 x (60/24 - 16/24 - 21/24) + 3/4] - 1/3} =
= 2/13 x [5/2 x (6/23 x 23/24 + 3/4) - 1/3] =
= 2/13 x [5/2 x (1/4 + 3/4) - 1/3] =
= 2/13 x (5/2 x 4/4 - 1/3) =
= 2/13 x (5/2 x 1 - 1/3) =
= 2/13 x (5/2 - 1/3) =
= 2/13 x (15/6 - 2/6) =
= 2/13 x 13/6 =
= 2/6 =
= 1/3
= 2/13 x [5/2 x (6/23 x 23/24 + 3/4) - 1/3] =
= 2/13 x [5/2 x (1/4 + 3/4) - 1/3] =
= 2/13 x (5/2 x 4/4 - 1/3) =
= 2/13 x (5/2 x 1 - 1/3) =
= 2/13 x (5/2 - 1/3) =
= 2/13 x (15/6 - 2/6) =
= 2/13 x 13/6 =
= 2/6 =
= 1/3
marianvopsitoru1:
Multumesc frumoas
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Biologie,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă